ISOLATION AND PURIFICATION OF LYSOZYME FROM THE HEN EGG WHITE - S. S.; I. I.; A. M.; M. G.; V. A. (Biotechnologia Acta, 2015)
The aim of the research was the development of the method of lysozyme isolation from hen egg proteins. Lysozyme was isolated by differential heat denaturation of proteins with changing of the medium pH value, followed by neutralization, dialysis and additional purification by gel chromatography on Sephadex G-50. Activity was determined by bacteriolytic method (with Micrococcus lysodeikticus 4698 as a substrate). The enzyme purity and molecular mass were determined using SDS-electrophoresis and massspectrometry.